The Effect Of Educational Video On Knowledge Of Personal Protective Equipment For Road Barrier Workers Of Pt X Klaten - Widyawati, Estiningtyas; Fauzi, Rachmawati Prihantina; Ismayenti, Lusi (Jurnal Kesehatan Manarang, 2025)
PT X Klaten is a subcontractor in the road construction project, responsible for manufacturing road barriers that function as safety signs and lane dividers. This type of work involves multiple occupational hazards, such as injuries from sharp materials, falling objects, and accidents involving project vehicles, particularly during night shifts. An initial survey revealed that 70% of workers had limited knowledge of Personal Protective Equipment (PPE), contributing to low compliance and an increased risk of workplace accidents. This study aims to examine the effect of educational videos on improving PPE knowledge among road barrier workers at PT X Klaten. A quasi-experimental design was employed using a pre-test and post-test control group. Total sampling was applied to recruit 50 respondents, who were equally divided into experimental and control groups. The intervention consisted of a two-week educational video program incorporating animations and real-life demonstrations that explained the types, functions, and proper use of PPE in construction settings. Data were collected using structured questionnaires and analyzed through Paired Sample T-tests and Independent Sample T-tests. The results have shown a significant increase in PPE knowledge in the experimental group, p-value = 0.001 (p ≤ 0.05), while the control group exhibited no significant change, p-value = 0.422 (p> 0.05). The comparison between groups has revealed a statistically significant difference in post-test scores, Sig (2-tailed) value = 0.017 (p ≤ 0.05). These findings demonstrate that educational videos are an effective medium for enhancing PPE-related knowledge among construction workers. This approach can be applied more broadly in other high-risk industries as a practical strategy to improve occupational safety, increase PPE compliance, and reduce the incidence of work-related accidents.